Analisis Kelayakan Usaha Budidaya Udang Vannamei (Litopenaeus vannamei) Sistem Intensif di Desa Sawojajar Kecamatan Wanasari, Kabupaten Brebes - Wiranata, Bangkit; Wahyu Prasetyo, Taufiq; Rahmi Richana, Farica; Ayu Azizah, Mutiara (Program Studi Budidaya Perairan Universitas Mataram, 2022)
Vannamei shrimp has important economic value and has been widely cultivated. The feasibility analysis of vannamae shrimp farming needs to be done to assess business and investment opportunities and protect the risk of loss. The purpose of this study was to analyze the feasibility of vannamei shrimp farming with an intensive system in Sawojajar Village, Wanasari District, Brebes Regency. Research data collection was carried out in March-April 2022 in Sawojajar Village, Wanasari District, Brebes Regency. This research method uses an active survey with purposive sampling. Analysis of financial aspects with investment criteria such as break event point (BEP), R/C ratio and Payback Period (PP). The results of the calculation of the BEP value of 220,562,263, Revenue cost ratio (R/C ratio) with a value of 2.32. and Payback Period (PP) of 0.43. In general, the feasibility analysis of vannamei shrimp farming in Sawojajar Village, Wanasari District, Brebes Regency is categorized as feasible to run.